SARS-CoV-2 Spike-Heat Shock Protein A5 (GRP78) Recognition may be Related to the Immersed Human Coronaviruses - Elfiky, Abdo A. (Frontiers in Pharmacology, 2020)
The human coronavirus (HCoV), SARS-CoV-2, caused more than 34 M confirmed infections from which more than 1M deaths are reported until now (the WHO situation report-154). The current pandemic causes severe socio-economic burden. Due to the importance of understanding of the mode of recognition and viral entry, spike protein shed drug designers as the first look protein target with the first released solved structure on 26 February 2020 (PDB ID: 6VSB). It is proposed that the recognition site for GRP78 is found in SARS-CoV-2 and the immersed human coronaviruses but experimental validation is still required.